Can Pay-for-Performance to Primary Care Providers Stimulate Appropriate Use of Antibiotics? - Anders Anell; Jens Dietrichson; Lina Maria Ellegård (Lund University, School of Economics and Management, Department of Economics, 2016)
Antibiotics resistance is a major threat to public health. We examine if pay-for-performance (P4P) to primary care providers stimulates appropriate prescription of antibiotics; specifically, if P4P induces a substitution of narrow-spectrum antibiotics for broad-spectrum antibiotics (which contribute more to resistance) in the treatment of children with respiratory tract infections (RTI). During 2006-2013, a subset of Swedish healthcare authorities introduced antibiotics-related P4P in their reimbursement schemes for care providers. We employ municipality-level data covering all purchases of RTI antibiotics in a difference-in-differences analysis, and find that P4P significantly increased the share of narrow-spectrum antibiotics. There were no signs that physicians tried to game the system by increasing overall antibiotics use.
Keywords: D23; H73; I11; I18; J33; J38; 330; pay-for-performance; antibiotics resistance; primary care